Fix and replace technique in elderly acetabular fractures - Delgadillo, Camilo A.; Pesantez, Rodrigo (Journal of Musculoskeletal Surgery and Research)
Fragility fractures in the pelvis and lower limbs increase morbidity and mortality. The surgical treatment and rehabilitation of acetabular fractures in the elderly are challenging due to weight-bearing limitations. With the “fix and replace” technique, the combined management of open reduction and internal fixation of the acetabular fracture and total hip replacement could be beneficial, having high consolidation rates, long prosthesis survival, a mortality rate of 13% and early weight-bearing with good functional outcomes. This publication aimed to review the available literature on treating acetabular fractures in the elderly, with particular attention to the “fix and replace” technique.